2006
DOI: 10.3201/eid1207.060253
|View full text |Cite
|
Sign up to set email alerts
|

Tickborne Arbovirus Surveillance in Market Livestock, Nairobi, Kenya

Abstract: Numerous tickborne viruses, including Dhori virus and foot-and-mouth disease virus, were isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 24 publications
3
59
0
1
Order By: Relevance
“…in Cameroon and Cote d'Ivoire and a human in the Central African Republic, and Barur virus (BARV), which has been isolated from ticks and a rodent (Rattus rattus) in India, ticks, fleas and mosquitoes of several species in Kenya and ticks in Somalia. [9][10][11][12][13][14][15] Phylogenetic analysis of partial N (nucleoprotein) protein sequences indicates that KCV is also related to several other viruses that have been isolated from bats in Africa and Asia. 16,17 These include Mount Elgon bat virus (MEBV) isolated in 1964 from a horseshoe bat (Rhinolophus hildebrandtii) in Kenya, Oita virus (OITAV) isolated in 1972 also from a horseshoe bat (Rhinolophus cornutus) in Japan, Kolente virus (KOLEV) isolated in 1985 from a roundleaf bat (Hipposideros jonesi) and a pool of ticks (Amblyomma (Theileriella) variegatum) in Guinea, and Fikirini virus (FKRV) isolated in 2011 from a roundleaf bat (Hipposideros vittatus) in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…in Cameroon and Cote d'Ivoire and a human in the Central African Republic, and Barur virus (BARV), which has been isolated from ticks and a rodent (Rattus rattus) in India, ticks, fleas and mosquitoes of several species in Kenya and ticks in Somalia. [9][10][11][12][13][14][15] Phylogenetic analysis of partial N (nucleoprotein) protein sequences indicates that KCV is also related to several other viruses that have been isolated from bats in Africa and Asia. 16,17 These include Mount Elgon bat virus (MEBV) isolated in 1964 from a horseshoe bat (Rhinolophus hildebrandtii) in Kenya, Oita virus (OITAV) isolated in 1972 also from a horseshoe bat (Rhinolophus cornutus) in Japan, Kolente virus (KOLEV) isolated in 1985 from a roundleaf bat (Hipposideros jonesi) and a pool of ticks (Amblyomma (Theileriella) variegatum) in Guinea, and Fikirini virus (FKRV) isolated in 2011 from a roundleaf bat (Hipposideros vittatus) in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…DUGV has been reportedly isolated from several tick species, including A. gemma and R. pulchellus, the species from which Kupe virus was isolated (19,23,24). In the 1999 Kenya abattoir survey, DUGV was isolated from 4 species of ticks, A. variegatum, A. gemma, A. lepidum, and R. pulchellus (3). Although ≈1,000 specimens each of A. variegatum and A. lepidum were collected and tested in that study, no isolates of Kupe virus were found in those species, which suggested that vector hosts for DUGV and Kupe virus may differ (3).…”
Section: Discussionmentioning
confidence: 99%
“…Isolates of viruses were obtained from pools of ticks collected at abattoirs in Nairobi, Kenya, as described (3). The K611 isolate used in this study was obtained from a pool of Amblyomma gemma ticks in October 1999.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations